2018
DOI: 10.15415/jptrm.2018.62008
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis and Antidiabetic Activity of Novel Sulfamoyl Benzamide Derivatives as Glucokinase Activators

Abstract: The present work has been planned to design, synthesize and evaluate the antidiabetic potential of a series of sulfamoyl benzamide derivatives as potential glucokinase (GK) activators. A new series of sulfamoyl benzamide derivatives was synthesized starting from 3-nitrobenzoic acid and characterized. In silico docking studies were performed to determine the binding interactions for the best fit conformations in the allosteric site of GK enzyme. Based on the results of in silico studies, the selected molecules … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Systematic exploration of the structural component of AM-2394 resulted in the identification of multiple compounds with improved solubility than AM-2394 (Kohn et al, 2016), with acceptable clearance and bioavailability in rat models. N-pyridin-2-yl benzamide analogs (62) were reported as allosteric activators of GK (Grewal, Kharb, et al, 2018;Grewal, Sharma, et al, 2018). The docking studies supported the binding of these analogs in the allosteric site of GK and they exhibited a significant reduction in blood glucose levels.…”
Section: Pyridine Derivativesmentioning
confidence: 81%
See 2 more Smart Citations
“…Systematic exploration of the structural component of AM-2394 resulted in the identification of multiple compounds with improved solubility than AM-2394 (Kohn et al, 2016), with acceptable clearance and bioavailability in rat models. N-pyridin-2-yl benzamide analogs (62) were reported as allosteric activators of GK (Grewal, Kharb, et al, 2018;Grewal, Sharma, et al, 2018). The docking studies supported the binding of these analogs in the allosteric site of GK and they exhibited a significant reduction in blood glucose levels.…”
Section: Pyridine Derivativesmentioning
confidence: 81%
“…Kobayashi et al (2021) tested the toxicity of TMG123 as a GKA and reported that long-lasting hypoglycemia in rats is harmful to spermatogenesis and the testicular damage does not recover. A series of sulfamoyl benzamide derivatives as potential glucokinase (GK) activators were designed and synthesized by Grewal, Kharb, et al (2018)) and Grewal, Sharma, et al (2018) in vivo and in silico docking study of the synthesized compounds, revealed that compound 83 has a strong antidiabetic activity (Grewal, Kharb, et al, 2018;Grewal, Sharma, et al, 2018).…”
Section: Other Gk Activatorsmentioning
confidence: 99%
See 1 more Smart Citation